2000
DOI: 10.1007/bf02347050
|View full text |Cite
|
Sign up to set email alerts
|

Detection and multichannel SVD-based filtering of trigeminal somatosensory evoked potentials

Abstract: Very weak and noisy trigeminal somatosensory evoked potentials (TSEPs) are considered, which are successfully evoked by electrical stimulation of the trigeminal nerve of 15 patients with endosseous oral implants. As TSEP analysis provides an objective means of assessing neuronal function, it is considered to be a promising tool for investigating tactile sensation through anchoring implants in bone. For this purpose, a study of TSEP signals acquired from patients with endosseous oral implants has been carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…By triggering sweeps in the electroencephalogram by means of an implant stimulation device and by cumulating and advanced analysis of the sweeps, one can finally note significant waves. The experiments indicate that it is indeed endosseous and/or periosteal receptors around the implants, which convey the sensation (8, 41).…”
Section: Tactile Function Of Oral Implantsmentioning
confidence: 95%
See 2 more Smart Citations
“…By triggering sweeps in the electroencephalogram by means of an implant stimulation device and by cumulating and advanced analysis of the sweeps, one can finally note significant waves. The experiments indicate that it is indeed endosseous and/or periosteal receptors around the implants, which convey the sensation (8, 41).…”
Section: Tactile Function Of Oral Implantsmentioning
confidence: 95%
“…Evidence can also be found by non‐invasive approaches for evaluation of oral tactile function. The first approach is the recording of the so‐called trigeminal somatosensory evoked potentials (TSEP) after stimulation of receptors in the oral cavity (7, 8). This set‐up has the advantage of obtaining information on the cortical response of the trigeminal afferent system upon non‐invasive stimulation of oral receptors.…”
Section: Neurophysiological Versus Psychophysical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that a neurophysiological peripheral feedback pathway can be partly restored [16,[19][20]. Such an assumption is supported by findings showing that two types of stimulation (pressure and strokes by a toothbrush) of an OI thumb prosthesis resulted in cortical activation on both sides of the somatosensory cortex, using functional magnetic resonance imaging of the brain [21].…”
Section: Introductionmentioning
confidence: 80%
“…The involvement of the bone innervation in mechanical perceptions is still a controversial subject . The function of bone innervation may be limited to vasoregulatory and bone remodeling processes, whereby most nerve fibers have free nerve endings in the bone connected to the endosteum with vessels or with connective tissue components and may also respond to pressure and pain stimuli . In animal experiments, it has been shown that implant materials are surrounded by nerve fibers in the area of the bone/implant interface .…”
Section: Resultsmentioning
confidence: 99%